2010
DOI: 10.1371/journal.pone.0010386
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Value of Zinc Supplementation in Acute and Persistent Diarrhea: A Systematic Review

Abstract: BackgroundFor over a decade, the importance of zinc in the treatment of acute and persistent diarrhea has been recognized. In spite of recently published reviews, there remain several unanswered questions about the role of zinc supplementation in childhood diarrhea in the developing countries. Our study aimed to assess the therapeutic benefits of zinc supplementation in the treatment of acute or persistent diarrhea in children, and to examine the causes of any heterogeneity of response to zinc supplementation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
22

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 67 publications
1
81
0
22
Order By: Relevance
“…Zinc deficiency is a major determinant factor of immunity and low weight in developing countries, and both are related with the duration of diarrhea (13)(14)(15). The administration of zinc was shown to reduce the duration of the diarrhea as well as frequency and amount of the stool in randomized controlled trials and reviews (16)(17)(18). The World Health Organization recommends routine use of zinc supplementation, at a dosage of 20 mg per day for children older than six months.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc deficiency is a major determinant factor of immunity and low weight in developing countries, and both are related with the duration of diarrhea (13)(14)(15). The administration of zinc was shown to reduce the duration of the diarrhea as well as frequency and amount of the stool in randomized controlled trials and reviews (16)(17)(18). The World Health Organization recommends routine use of zinc supplementation, at a dosage of 20 mg per day for children older than six months.…”
Section: Discussionmentioning
confidence: 99%
“…Los niños bien nutridos de países con bajo riesgo de déficit de zinc no tienen beneficios y la gravedad de la diarrea tampoco parece estar relacionada con este efecto. En menores de 6 meses, se necesitan más estudios para justificar la suplementación de zinc, considerando el riesgo de vómito y un posible mayor (5,31,32,33,34,35) riesgo que beneficio.…”
Section: Zincunclassified
“…Zinc represents a new intervention for treating diarrhoea, which activates transcription factor NF-κB and modulates host defence and since its deficiency is associated with high inflammation and bad outcomes in fighting bacterial infections (71). Several studies showed that 10 -20 mg zinc per day for 10 -14 days significantly reduces the gravity and duration of diarrhoea in small children (72,73).…”
Section: Parasitic-helmints Nematodesmentioning
confidence: 99%